Newly designed resorcinolate binding for Ru(II)- and Re(I)- polypyridyl complexes on oleic acid capped tio2 in non-aqueous solvent: prolonged charge separation and substantial thermalized 3MLCT injection - Banerjee, Tanmay; Kaniyankandy, Sreejith; Das, Amitava; Ghosh, Hirendra Nath (Journal of Physical Chemistry C, 2013)
Femtosecond pump–probe spectroscopic studies on a series of newly synthesized resorcinol-based Ru(II) and Re(I) complexes on oleic acid capped TiO2 nanoparticles have been carried out in chloroform, and the results are compared with those of the catechol analogues. The ruthenium complex shows biexponential injection; the second component arises due to injection from the thermally equilibrated 3MLCT states as a result of a weaker strength of the resorcinolate binding. Also, in comparison with catechol binding, as a result of a greater diffusion of the injected electrons into TiO2, the back electron transfer (BET) is slowed down significantly for the ruthenium complex. These are distinctive observations for any mononuclear ruthenium–polypyridyl–enediol complex reported thus far. However, the rhenium complex educes single exponential ultrafast injection (<120 fs) because of apparent injection in a high density of states and shows the most prominent results with ∼50% slowdown in the charge recombination rate as compared to the analogous catechol bound system. These results exemplify the probable development of highly capable sensitizer dyes with resorcinol as the anchoring group for the development of efficient dye-sensitized solar cells.

Synthesis, steady-state, and femtosecond transient absorption studies of resorcinol bound ruthenium(ii)- and osmium(ii)-polypyridyl complexes on nano-TiO2 surface in water - Banerjee, Tanmay; Kaniyankandy, Sreejith; Das, Amitava; Ghosh, Hirendra Nath (Inorganic Chemistry, 2013)
The synthesis of two new ruthenium(II)- and osmium(II)-polypyridyl complexes 3 and 4, respectively, with resorcinol as the enediol anchoring moiety, is described. Steady-state photochemical and electrochemical studies of the two sensitizer dyes confirm strong binding of the dyes to TiO2 in water. Femtosecond transient absorption studies have been carried out on the dye–TiO2 systems in water to reveal <120 fs and 1.5 ps electron injection times along with 30% slower back electron transfer time for the ruthenium complex 3. However, the corresponding osmium complex 4 shows strikingly different behavior for which only a <120 fs ultrafast injection is observed. Most remarkably, the back electron transfer is faster as compared to the corresponding catechol analogue of the dye. The origin and the consequences of such profound effects on the ultrafast interfacial dynamics are discussed. This Article on the electron transfer dynamics of the aforesaid systems reinforces the possibility of resorcinol being explored and developed as an extremely efficient binding moiety for use in dye-sensitized solar cells.